Galaxy And Mass Assembly (GAMA): Spectroscopic analysis - Hopkins, A; Driver, S; Brough, S; Owers, MS; Bauer, A; Gunawardhana, M; Cluver, M; Colless, M; Foster, C; Lara-Lopez, M; Roseboom, I; Sharp, R; et al. (2013)
The Galaxy And Mass Assembly (GAMA) survey is a multiwavelength photometric and spectroscopic survey, using the AAOmega spectrograph on the Anglo-Australian Telescope to obtain spectra for up to ~300000 galaxies over 280 square degrees, to a limiting magnitude of r_pet < 19.8 mag. The target galaxies are distributed over 0